An ultrastructural and light microscopic study of melanocyte differentiation in chick embryos - Stander, Cornelia Steynberg (Division of Cell Biology, 2018)
The embryonic source and chemical nature of those factor/s directing the in vivo differentiation of melanocytes from crest cells are as yet unknown. To begin to address this issue, it is important to establish exactly when and where these signa/s first exert their effects. Therefore, in the present study, overtly differentiated melanocytes containing melanin were quantitated in developing Black Australorp X New Hampshire Red chick embryos. In contrast to previous studies, it was found that embryos synthesize melanin from as early as Day 5 of development, and that at this stage, the melanocytes are predominantly dermally located. Between 5 and 8 days, the numbers of both dermal and epidermal melanocytes increase, after which the dermal melanocyte population declines rapidly while the number of epidermal melanocytes continues to increase. These findings suggest that premelanocytes do not have to be epidermally located to initiate terminal differentiation and implicate the dermis as a possible source of melanocyte inducing factor/s. The next step was to examine stages of development prior to the onset of pigment production. For this reason, tyrosinase was purified for use as antigen in the production of a polyclonal antibody. The antibody was tested for specificity by western blotting, - immunocytochemistry and immunoinhibition procedures. Lack of specificity was demonstrated, rendering it unsuitable as an antibody marker for early melanocytes. Fowl melanocytes are thought to differentiate into either eumelanosome- or pheomelanosome synthesizing cells. To test the validity of this concept, embryonic skin of the red/black cross breed were screened for possible mixed type melanocytes by electron microscopy. The melanocytes contained melanosomes with a matrix of irregularly arranged filaments amongst typical eumelanogenic melanosomes. This suggests that these chick melanocytes may synthesize both eumelanosomes and pheomelanosomes in single cells. In a further study on pure breeding New Hampshire Reds, it was found that the melanocytes contained a mixture of typical and less typical pheomelanosomes. Outer membrane indentations in the latter melanosome type suggest that tyrosinase may enter these pheomelanosomes by a mechanism related to that proposed for the melanosomes of goldfish.